Analisis Yohanes 14:16 Suatu Kajian Apologetika Doktrin Roh Kudus - Daud Balang; Eko Chandra Setiawan (Shema: Jurnal Teologi Injili dan Pendidikan Kristen, 2022)
Criticism comes to the text of John 14:16. Criticism comes especially to the phrase "one helps another". Criticism comes with various types of interpretation. From various interpretations, there is an assumption that the phrase "another helper" in John 14:16 does not refer to the Holy Spirit. There are four critics who doubt the phrase. Criticism of theology, interpretation, etymology and equating of texts with books of other faiths. An analysis of John 14:16 is needed to answer the criticism of the phrase "another helper" in John 14:16. The analysis becomes an apologetic study of this criticism. With apologetics, in the end this article answers that the phrase "a helper to another" is the Holy Spirit. Abstrak Bahasa Indonesia Kritisi datang kepada teks Yohanes 14:16. Kritisi datang khususnya kepada frasa “seorang penolong yang lain”. Kritisi datang dengan berbagai macam jenis penafsiran. Dari berbagai macam penafsiran, terdapat asumsi bahwa frasa “seorang penolong yang lain” dalam Yohanes 14:16 bukanlah merujuk kepada Roh Kudus. Terdapat empat kritisi yang meragukan frasa tersebut. Kritisi teologi, interpretasi, etimologi dan penyepadanan teks dengan kitab kepercayaan lain. Dibutuhkan analisis terhadap Yohanes 14:16 untuk menjawan kitisi frasa “seorang penolong yang lain” dalam Yohanes 14:16. Analisisnya menjadi sebuah kajian apologetika terhadap kritisi tersebut. Dengan apologetika, pada akhirnya artikel ini menjawab bahwa frasa “seorang penolong yang lain” adalah Roh Kudus.